2022
DOI: 10.3390/molecules28010057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Chiral Resolution and Enantiomers Absolute Configuration of 4-Nitropropranolol and 7-Nitropropranolol

Abstract: We recently identified 6-nitrodopamine and other nitro-catecholamines (6-nitrodopa, 6-nitroadrenaline), indicating that the endothelium has the ability to nitrate the classical catecholamines (dopamine, noradrenaline, and adrenaline). In order to investigate whether drugs could be subject to the same nitration process, we synthesized 4-nitro- and 7-nitropropranolol as probes to evaluate the possible nitration of the propranolol by the endothelium. The separation of the enantiomers in very high yields and excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The absolute configuration of 1 was assigned as (5R,1′R) by a single-crystal X-ray diffraction experiment using Cu-Kα radiation [16] were observed in the same CDCl3 solvent, which suggested that 2 could be a 5-epimer of 1 (Table 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) was determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4, and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 for 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute configuration of 1 was assigned as (5R,1′R) by a single-crystal X-ray diffraction experiment using Cu-Kα radiation [16] were observed in the same CDCl3 solvent, which suggested that 2 could be a 5-epimer of 1 (Table 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) was determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4, and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 for 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 shared the same planar structure as 1 and was further identified by 2D NMR spectra, including 1 1). The absolute configuration of the secondary hydroxylated carbon (C-1′) wa determined using a modified Mosher's method [17][18][19][20]. The chemical shifts for H-2′, H-4 and H-7 of 1a and 1b were measured as δH 1.49, 4.94, 2.38 for 1a, and δH 1.44, 4.96, 2.49 fo 1b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its electron-withdrawing nature, the nitrogroup may provide functional diversity (Kamisaki et al, 1998). ()-4-Nitro-propranolol and ()-7-nitro-propranolol have been synthetized as racemic mixtures, and the enantiomers purified following chiral high-pressure liquid chromatography (Sparaco et al, 2022). Here, it was investigated the effects of (±)-propranolol, ()-4-NO2-propranolol, and ()-7-NO2propranolol and their respective (R)-and (S)-enantiomers on both the spontaneous atrial rate and the positive chronotropic effects induced by noradrenaline, adrenaline, and 6-ND.…”
mentioning
confidence: 99%
“…Due to its electron-withdrawing nature, the nitrogroup may provide functional diversity. 4-nitro-propranolol and 7-nitro-propranolol have been synthetized as racemic mixtures, and the enantiomers purified following chiral high pressure liquid chromatography method (Sparaco et al, 2022). Here, it was investigated the effect of both propranolol analogues, and their respective enantiomers (S)-(+)-4-NO2-propranolol, (R)-(-)-4-NO2-propranolol, (S)-(+)-7-NO2-propranolol and (R)-(-)-7-NO2-propranolol), on the rat isolated right atrium basal rate and on the positive chronotropic effects induced by 6-ND, dopamine, noradrenaline, and adrenaline.…”
mentioning
confidence: 99%